Clock Gating Techniques for Power Optimization in PCIe TCP Header Generator Logic - Gaurav Yadav (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article comprehensively investigates applying clock gating techniques for optimizing power consumption in PCIe TCP header generator logic. As networking hardware faces increasing performance demands alongside energy constraints, efficient power management at the circuit level becomes critical. The article explores various clock gating methodologies, from fine-grained to coarse-grained approaches, and their implementation in ASIC and FPGA platforms. Through detailed architecture analysis, the article identifies key functional blocks within the TCP header generator that are particularly amenable to clock gating optimization. The article addresses significant challenges, including timing violations, synchronization issues across clock domains, and verification complexity. Advanced techniques such as activity-based adaptive clock gating and predictive enable generation and integration with complementary power-saving methods are thoroughly evaluated. The article presents experimental results demonstrating substantial dynamic power reductions while maintaining full line-rate performance with minimal latency overhead. The article contributes practical implementation guidelines, debugging methodologies, and a framework for power-complexity trade-off assessment specifically tailored for high-speed networking components. Collectively advance the field of energy-efficient hardware design for next-generation communication infrastructure.